PPAK UTHM Connect System - NURUL SYAZANA ABDU GHANI; MAT REJAB, MAZIDAH (Applied Information Technology And Computer Science, 2025)
The Pusat Pendidikan Awal Kanak-Kanak (PPAK) UTHM, encompassing Taska Hikmah UTHM and Tadika Khalifah Junior, aims to modernize operations with a centralized digital platform. This platform will streamline administrative tasks like payment tracking, attendance logging, and communication via memos and notifications. Replacing the current manual system, it reduces errors, inefficiencies, and reliance on physical records. Parents will gain real-time updates on their child’s progress, improving engagement and communication. The platform, developed for web will undergo rigorous testing to ensure usability and will support education for children aged 2-6, aligned with PERMATA and KSPK syllabi. Expected outcomes include operational efficiency, enhanced parent-teacher collaboration, and a stronger connection between home and school, fostering a supportive learning environment.